MANAJEMEN DAKWAH HUMANIS PERSPEKTIF GUS DUR DALAM MEMBANGUN MASYARAKAT MULTIKULTURAL - Hanum Muyassaroh; Lilin Nur Indah Sari; Erni Lasari; Anang Sholikhudin (CV. BAROKAH PUBLISHER, 2026)
This study examines Gus Dur’s perspective on humanistic da’wah management as an inclusive approach to strengthening social harmony within multicultural societies. The rise of intolerance and exclusive religious narratives in contemporary society has created challenges for maintaining social cohesion in Indonesia’s multicultural context. Therefore, a humanistic and inclusive da’wah approach is needed to strengthen the values of tolerance, pluralism, and humanity in social life. This study aims to analyze the concept of humanistic da’wah management according to Gus Dur and its relevance in multicultural society. This research uses a qualitative approach with the type of library research. The data were obtained from books, scientific journals, and various academic literature related to Gus Dur’s thoughts, da’wah management, pluralism, and Islamic humanism. Data analysis was conducted using descriptive-analytical techniques through data reduction, data presentation, and conclusion drawing. The results of the study indicate that Gus Dur’s da’wah management emphasizes humanistic, pluralistic, and cultural approaches in delivering Islamic values. Dakwah is not only understood as a religious activity but also as a means of social transformation to create harmonious social relations. Gus Dur’s da’wah strategy prioritizes dialogue, tolerance, and respect for local culture. Furthermore, the concept of humanistic da’wah is considered relevant in addressing intolerance and strengthening social integration in multicultural societies. In conclusion, Gus Dur’s humanistic da’wah management offers an inclusive and moderate model of Islamic preaching that is relevant to contemporary Indonesian society.